Crystallization study of rare earth and molybdenum containing nuclear waste glass ceramics. Issue 9 (12th March 2019) - McCloy, John S.; Riley, Brian J.; Crum, Jarrod; Marcial, José; Reiser, Joelle T.; Kruska, Karen; Peterson, Jacob A.; Neuville, Daniel R.; Patil, Deepak S.; Saleh, Muad; Barnsley, Kristian E.; Hanna, John V.
Abstract: A glass‐ceramic waste form is being developed for immobilization of waste streams of alkali (A), alkaline‐earth (AE), rare earth (RE), and transition metals generated by transuranic extraction for reprocessing of used nuclear fuel. Benefits over an alkali borosilicate waste form are realized by the partitioning of the fission product fraction insoluble in glass into a suite of chemically durable crystalline phases through controlled cooling, including (AE, A, RE)MoO4 (powellite) and (RE, A, AE)10 Si6 O26 (oxyapatite). In this study, a simplified 8‐oxide system (SiO2 ‐Nd2 O3 ‐CaO‐Na2 O‐B2 O3 ‐Al2 O3 ‐MoO3 ‐ZrO2 ) was melted, then soaked at various temperatures from 1450 to 1150°C, and subsequently quenched, in order to obtain snapshots into the phase distribution at these temperatures. For these samples, small angle X‐ray and neutron scattering, quantitative X‐ray diffraction, electron microscopy, 23 Na nuclear magnetic resonance, Nd 3+ visible absorption, and temperature‐dependent viscosity were characterized. In this composition, soak temperatures of ≲ 1250°C were necessary to nucleate calcium molybdate ( 10‐20 nm in diameter). Further cooling produced oxyapatite and total crystallization increased with lower soak temperatures. Both Na and Nd entered the crystalline phases with lower‐temperature soak conditions. Slow cooling or long isothermal treatments at 975°C produced significantly higher crystal fractions.